2011
DOI: 10.1002/ejlt.201000535
|View full text |Cite
|
Sign up to set email alerts
|

Oil composition of advanced selections from an olive breeding program

Abstract: Fifteen genotypes coming from crosses between the cultivars Arbequina, Frantoio and Picual were selected on the basis of their agronomic characteristics in a breeding program initiated in 1991. In the present work, the main components of the olive oil of these 15 advances selections have been characterized and compared to their genitors. A wide range of variation was observed for all the fatty acids, minor components and related characteristics evaluated, with significant differences between genotypes for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 25 publications
6
53
0
Order By: Relevance
“…The extensive genetic patrimony of the olive tree is currently used in different olive breeding programs, but only recently includes the sensory properties of VOO as main traits, in addition to the agronomic traits [25,27,30]. Regarding these sensory properties, the natural variation of aroma compounds in VOO was studied using the WOGC olive cultivar collection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive genetic patrimony of the olive tree is currently used in different olive breeding programs, but only recently includes the sensory properties of VOO as main traits, in addition to the agronomic traits [25,27,30]. Regarding these sensory properties, the natural variation of aroma compounds in VOO was studied using the WOGC olive cultivar collection.…”
Section: Resultsmentioning
confidence: 99%
“…This high genetic diversity of the olive germplasm collection could be very useful to recuperate old cultivars which produce oils with outstanding aromas, or for the selection of parents in breeding programs, in order to find new cultivars with improved olive oil aroma. In this sense, olive breeding programs are lately addressing the selection of cultivars, based on the sensory and nutritional qualities of VOO [25,26], in addition to the traditional agronomic traits [27]. For this purpose, the aim of this work was to evaluate the volatile composition and presumed aroma properties of the oils from a representative sample of cultivars from WOGC.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit and oil quality traits are generally considered only in the last selection steps. Several authors have reported improved cultivars/ advanced selections with enhanced oleic acid, tocopherol, and/or total phenolic contents (Manaï et al, 2007;Baccouri et al, 2007;Ripa et al, 2008;León et al, 2011;De la Rosa et al, 2013). Practically no breeding research has been conducted on other oil quality traits such as squalene and phytosterols.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Tunisia, an olive breeding programme started in 1989 with a cross between Tunisian and foreign cultivars. This created new cultivars with a quality of oil superior to that of Chemlali (the main olive cultivar in the country, characterized by low levels of oleic acid) and characteristics close to the standards of the international market (Baccouri et al, 2007;León et al, 2011;Manai et al, 2007;Manai et al, 2008;Rjiba et al, 2010). The large variability in all the components of olive oil in these advanced selections suggests that diversity in olive oil composition could be obtained in any crossbreed progeny.…”
Section: Genetic Modification Of Olive Cultivars: Crossbreedingmentioning
confidence: 99%
“…León et al (2011) selected fifteen genotypes from crosses between the cultivars Arbequina, Frantoio and Picual on the basis of their agronomic characteristics. In this work, the main components of the olive oil were characterized and compared with their genitors.…”
Section: Genetic Modification Of Olive Cultivars: Crossbreedingmentioning
confidence: 99%